Scientific opinion on the safety of smoke flavouring Primary Product SmokEz Enviro 23 - 2012 Update - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal, 2012)
The EFSA CEF Panel updated the safety assessment of the smoke flavouring Primary Product SmokEz Enviro 23. In 2009, the Panel concluded that the margins of safety for this Primary Product were insufficient and the proposed use levels were considered of safety concern. After the opinion of 2009 the Panel received new data i.e. new use levels, chemical data and a new 90-day toxicity study, which resulted in this update of the previous opinion. The new chemical data provided demonstrate that the test material used in the new 90-day toxicity study is representative of the Primary Product evaluated by EFSA. Based on the findings from the 90-day study submitted in 2009 and from the newly submitted one, the Panel derived a NOAEL for Primary Product SmokEz Enviro 23 of 598 mg/kg bw/day based on absolute and relative kidney weight changes in female rats. Based on newly submitted normal use levels, the margins of safety are 62 and 77 (total dietary exposure) and 65 and 89 (use in traditionally smoked foods only) depending on the exposure scenario used. Given that these margins of safety are based on 90-day toxicity studies, and given the absence of data on reproduction, developmental toxicity and of long term studies, it is concluded that the uses and use levels of Primary Product would require a larger margin of safety. The Panel concluded that the proposed use of the Primary Product at the uses and use levels specified is of safety concern.